Mindfulness and Physical Disease: A Concise Review - Greeson, Jeffrey M. (Curr Opin Psychol, 2018)
Many of today’s most common, chronic, and costly diseases – from high blood pressure, to chronic pain – are related to stress. Mindfulness, considered a state, a trait, and a training, might help treat or prevent stress-related physical symptoms. A concise review of current scientific evidence shows that both higher levels of trait mindfulness as well as mindfulness training are associated with better psychological well-being, coping, and quality of life. Effects on objective measures of disease, however, are often non-significant or await replication. Larger trials with active control groups, clear diagnostic criteria, objective outcome measures, and longer-term follow-up are needed to generate better quality evidence. Yet, many studies do support integrating mindfulness into health care as part of self-care and disease management.